Vertical heterogeneity of hydrocarbon-degrading bacteria in a core sediment sample from the Central Indian Ridge - Hao, Tong; Cui, Zhisong; Luan, Xiao; Zhou, Guangzhu; Li, Yingchao; Liu, Jinyan; Chen, Junhui; Wang, Zongling (Frontiers in Marine Science, 2023)
Hydrocarbons are ubiquitous in marine environments and might fuel hydrocarbon-metabolizing microbes in the ocean. Numerous studies have documented microbial hydrocarbon degradation in water columns and deep-sea surface sediment. However, the degradation potential and biogeochemical cycling of hydrocarbons in subsurface sediments remain largely unknown. In this study, we used two different hydrocarbons, n-hexadecane (HEX) and methylcyclohexane (MCH), to investigate the distribution and diversity of hydrocarbon-consuming bacteria in a core sediment sample from the Central Indian Ridge (CIR), which is adjacent to mid-ridge hydrothermal vents in the Indian Ocean. We observed different vertical profiles of HEX- and MCH-degrading bacteria in the core sediments. Specifically, HEX-degrading bacteria were universally distributed, while MCH-degrading bacteria were found only in the intermediate layers of the core sediments. Changing factors including dissolved oxygen might affect the natural distribution of different hydrocarbon consumers. We found that a novel species of the genus C1-B045 might play a pivotal role in metabolizing MCH in the CIR deep biosphere. Through amino acid identity comparison with published sequences, we determined that C1-B045 harbors two novel classes of cyclohexanone monooxygenases involved in MCH metabolism. This study sheds light on the structure and function of hydrocarbon-consuming microbes in deep biospheres.